La Parusia e la sua anticipazione nella storia, nell'evento del Cristo Crocifisso e Risorto - Bordoni, Marcello 1930-2013 (2001)
This contribution intends to offer a response to the «eschatological question». It intends gathering-through contemporary questions of our times seen in the light of the christological faith centered in the Paschal Event and in the Parusia-clarifying elements of the complex relationship between «eschatology and history», the focal points of today’s debate. If «Israel was and is the people of hope», the first and the original eschatological religion, the Christian vision of history has strengthened this vision. But today, it seems, that there is an increasing lack of faith in the fact that «history» might be a «place of salvation» wherein redemption could be found, a fulfillment of man’s humanization, intertwined with his freedom.
Keywords: Eschatologie; Parusie